Prodigiosin - A Multifaceted Escherichia coli Antimicrobial Agent. - Tjaša Danevčič; Maja Borić Vezjak; Maša Zorec; David Stopar (PLoS ONE, 2016)
Despite a considerable interest in prodigiosin, the mechanism of its antibacterial activity is still poorly understood. In this work, Escherichia coli cells were treated with prodigiosin to determine its antimicrobial effect on bacterial physiology. The effect of prodigiosin was concentration dependent. In prodigiosin treated cells above MIC value no significant DNA damage or cytoplasmic membrane disintegration was observed. The outer membrane, however, becomes leaky. Cells had severely decreased respiration activity. In prodigiosin treated cells protein and RNA synthesis were inhibited, cells were elongated but could not divide. Pre-treatment with prodigiosin improved E. coli survival rate in media containing ampicillin, kanamycin and erythromycin but not phleomycin. The results suggest that prodigiosin acts as a bacteriostatic agent in E. coli cells. If prodigiosin was diluted, cells resumed growth. The results indicate that prodigiosin has distinct mode of antibacterial action in different bacteria.